Implementation of Nursing Credentials and Recredentials by the Credentials Subcommittee at X Distric Hospital - Sugito; Luky Dwiantoro; Anggorowati; Muhammad Hasib Ardani; Madya Sulisno (Jurnal Berita Ilmu Keperawatan, 2023)
The results of the preliminary study indicated that the implementation of nursing credentials and recredentials by the credentials subcommittee in the hospital was not optimal. Not many studies had investigated  the problems that caused the implementation of nursing credentials and recredentials was not optimal. This research was very important to do to  explore more deeply about the problems that caused the credentials subcommittee  was not optimally  in the implementation of nursing credentials and recredentials. To explore the implementation of nursing credentials and recredentials by the credentials subcommittee in hospital. This study used a case study method. This study used a nonprobability sampling method with a purposive sampling approach. The research participants were three stakeholders in the hospital. Data collection methods with documentation and interviews. Data analysis method according to Miles and Huberman. The results of data analysis obtained four themes: The process of implementing credentials and recredentials through training, OSCA exams and mentoring, has not used OPPE and FPPE, has not been carried out regularly, the organisation is carried out after the nurse is accepted. The implementation of the results of nursing credentials and recredentials has no reward and punishment, not one perception with staffing, in nursing practice has not been detailed and has not been used in determining nurse incentives. Obstacles in the implementation of credentials and recredentials are the nursing committee structure that serves in other functional areas, there is no one perception about the implementation of nursing credentials and recredentials with management, Covid 19 pandemic, and the application of clinical authority. Efforts to overcome obstacles by approaching management, using credentials results to determine nurse incentives, socialization to nurses and management as well as coordinating and cooperating with other sections Conclusion: There are barriers in the implementation of nursing credentials and recredentials. Efforts are needed to overcome obstacles in the implementation of nursing credentials and recredentials.